An intravascular bioartificial pancreas device (iBAP) with silicon nanopore membranes (SNM) for islet encapsulation under convective mass transport - Song, Shang (Lab Chip, 2017)
Diffusion-based bioartificial pancreas (BAP) devices are limited by poor islet viability and functionality due to inadequate mass transfer resulting in islet hypoxia and delayed glucose-insulin kinetics. While intravascular ultrafiltration-based BAP devices possess enhanced glucose-insulin kinetics, the polymer membranes used in these devices provide inadequate ultrafiltrate flow rates and result in excessive thrombosis. Here, we report the silicon nanopore membrane (SNM), which exhibits a greater hydraulic permeability and a superior pore size selectivity compared to polymer membranes for use in BAP applications. Specifically, we demonstrate that the SNM-based intravascular BAP with ~10 and ~40 nm pore sized membranes support high islet viability (>60%) and functionality (<15 minute insulin response to glucose stimulation) at clinically relevant islet densities (5,700 and 11,400 IE/cm(2)) under convection in vitro. In vivo studies with ~10 nm pore sized SNM in a porcine model showed high islet viability (>85%) at clinically relevant islet density (5,700 IE/cm(2)), c-peptide concentration of 144 pM in the outflow ultrafiltrate, and hemocompatibility under convection. These promising findings offer insights on the development of next generation of full-scale intravascular devices to treat T1D patients in the future.